Supplementation with Alpha-Tocopherol and Ascorbic Acid to Nonalcoholic Fatty Liver Disease’s Statin Therapy in Men - Nikola Hadzi-Petrushev; Katerina Dimovska; Nikola Jankulovski; Dine Mitrov; Mitko Mladenov (Advances in Pharmacological Sciences)
Oxidative stress and inflammation contribute to the pathogenesis and progression of nonalcoholic fatty liver disease (NAFLD), and the control of lipid status by statins may help to stop the progression of NAFLD. We hypothesized that the addition of antioxidant vitamins C and E to atorvastatin therapy is associated with improved serum enzyme antioxidant status. NAFLD-related serum parameters and the activity of antioxidant enzymes, before and after 3 months of treatment, were determined in patients receiving atorvastatin alone or atorvastatin plus antioxidants. Compared to healthy controls, the patients, before receiving therapy, had increased catalase and glutathione reductase, with no significant difference in glutathione peroxidase activity. After the treatment, the levels of all three antioxidant markers were reduced to the same degree in both groups of patients, indicating therapy-induced lower level of reactive oxygen species production and/or improved nonenzymatic antioxidant mechanisms. Both therapies led to the normalization of the serum lipid profile and aminotransferase levels in the patients, but the reduction in CRP, although significant, did not reduce levels to those of the controls. The obtained results favor the notion that therapy with atorvastatin alone is equally efficient during the early stages of NAFLD, regardless of the addition of antioxidant vitamins. This trial is registered with TCTR20180425001.